2021
DOI: 10.1128/msphere.00646-21
|View full text |Cite
|
Sign up to set email alerts
|

Host-Environment Interplay Shapes Fungal Diversity in Mosquitoes

Abstract: The Asian tiger mosquito, Aedes albopictus , is the dominant mosquito species in the United States and an important vector of arboviruses of major public health concern. One aspect of mosquito control to curb mosquito-borne diseases has been the use of biological control agents such as fungal entomopathogens.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 87 publications
5
35
0
Order By: Relevance
“…Within the Basidiomycota, the majority of reads were associated with the order Tremellales that contrasts with previous observations that showed a dominance and prevalence of the order Agaricales in all of the water and Ae. albopictus mosquito samples (Tawidian et al 2021). Interestingly, we showed that P. citrinum was one of the most abundant and prevalent species across larvae.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Within the Basidiomycota, the majority of reads were associated with the order Tremellales that contrasts with previous observations that showed a dominance and prevalence of the order Agaricales in all of the water and Ae. albopictus mosquito samples (Tawidian et al 2021). Interestingly, we showed that P. citrinum was one of the most abundant and prevalent species across larvae.…”
Section: Discussionmentioning
confidence: 77%
“…Within the phylum Ascomycota, OTUs in the fungal orders Pleosporales were shared across all water and larvae samples as previously observed in Ae. albopictus (Tawidian et al 2021). In addition, some specific patterns were observed between larvae and water as the majority of reads was assigned to the orders Capnodiales and Hypocreales for water samples and Trichosphaeriales, Eurotiales and Capnodiales for larvae samples.…”
Section: Discussionmentioning
confidence: 99%
“…This paralleled previous study which reported the composition and diversity of fungal communities associated with A. albopictus larvae and their natural habitats. It can be explained by the ubiquity of Ascomycota in freshwater ecosystems, including larval habitats ( Tawidian et al, 2021 ). Aspergillus clavatus (Ascomycota: Trichocomaceae) was previously found to be an opportunistic pathogen of mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus and Ae. aegypti larvae (Tawidian et al, 2021;Zouache et al, 2022). However, it remains unclear whether similar patterns in fungal community assembly are observed in the larvae of other mosquito species.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquito larval breeding sites harbor rich bacterial and fungal communities that vary across large and small geographic scales (Gimonneau et al, 2014;Coon et al, 2016;Bascuñán et al, 2018;Shelomi, 2019;Tawidian et al, 2021). The microbiota associated with field-collected mosquito larvae is largely influenced by the bacterial community in the aquatic habitat they reside in.…”
Section: Introductionmentioning
confidence: 99%